Cartoon Chronicles: Nurturing Oratory Skills in Junior High: Kronik Kartun: Menumbuhkan Keterampilan Berbicara di SMP - Novi Aristanty; Dian Rahma Santoso (Academia Open, 2023)
This study aimed to assess the impact of utilizing cartoon movies as a learning medium in teaching monologue to enhance speaking abilities among junior high school students. Employing a pretest-treatment-posttest design within a pre-experimental study model, the research focused on a classroom using the cartoon movie "Ponyo" alongside the conventional program-based teaching method. The interactive and culturally rich Japanese cartoon with a theme centered on teen imagination was applied in the treatment, involving 29 students from class B. The results, based on monologue technique assessments, demonstrated favorable opinions from students regarding the cartoon movie medium. However, while the findings indicated an improvement in speaking abilities, the effect was not statistically significant. This study provides insights into the potential of cartoon movies as an engaging educational tool and suggests avenues for further research and instructional refinement. Highlights : The study explores the use of cartoon movies as a dynamic medium for enhancing monologue instruction in junior high school settings. While student opinions on the cartoon medium were positive, the research highlights a significant yet non-statistically significant improvement in speaking abilities, suggesting further avenues for exploration and instructional development. "Ponyo," a culturally rich Japanese cartoon, is employed to supplement traditional teaching methods, fostering interactive learning experiences. Keywords: Monologue Instruction, Cartoon Movies, Speaking Ability, junior High School, Educational Impact